Behavior dynamics of low-frequency MHD-fluctuations and main plasma parameters in U-3M torsatron in RF-heating mode - Pashnev, V.K.; Sorokovoy, E.L.; Petrushenya, A.A.; Ozherel’ev, F.I.; Baron, D.I. (Вопросы атомной науки и техники, 2016)
A significant decrease in the intensity of low-frequency MHD-activity is accompanied by sharp increase of plasma energy content in U-3M torsatron. Plasma is generated and heated by RF-fields with frequency of w = 0.8w(ci) and is in a mode of low frequency of collisions. A set of 15 magnetic sensors was installed in one of the poloidal cross-sections of torus. The poloidal component of magnetic field was registered. At some point of time there is a sharp decrease of MHD-activity of plasma with a simultaneous increase of plasma energy content. Существенное уменьшение интенсивности низкочастотной МГД-активности сопровождается резким повышением энергосодержания плазмы в торсатроне У-3М. Плазма создаётся и нагревается ВЧ-полями с частотой w = 0.8w(ci) и находится в режиме редких частот соударений. В одном из полоидальных сечений тора был установлен набор из 15 магнитных датчиков. Регистрировалась полоидальная компонента магнитного поля. В некоторый момент времени наблюдается резкое уменьшение МГД-активности плазмы при одновременном росте энергосодержания плазмы. Суттєве зменшення інтенсивності низькочастотної МГД-активності супроводжується різким підвищенням
енергозмісту плазми в торсатроні У-3М. Плазма створюється і нагрівається ВЧ-полями з частотою w = 0.8w(ci) і
знаходиться в режимі рідкісних частот зіткнень. В одному з полоідальних перетинів тора був встановлений
набір з 15 магнітних датчиків. Реєструвалася полоідальна компонента магнітного поля. В деякий момент часу
спостерігається різке зменшення МГД-активності плазми при одночасному зростанні енергозмісту плазми.